2015
DOI: 10.1002/2014gl062588
|View full text |Cite
|
Sign up to set email alerts
|

Heavy precipitation in a changing climate: Does short‐term summer precipitation increase faster?

Abstract: Climate models project that heavy precipitation events intensify with climate change. It is generally accepted that extreme day-long events will increase at a rate of about 6-7% per degree warming, consistent with the Clausius-Clapeyron relation. However, recent studies suggest that subdaily (e.g., hourly) precipitation extremes may increase at about twice this rate. Conventional climate models are not suited to assess such events, due to the limited spatial resolution and the need to parametrize convective pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
354
5
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 389 publications
(391 citation statements)
references
References 36 publications
29
354
5
3
Order By: Relevance
“…Analysis performed for the Wagner et al (2012) paper (personal communication) shows similar decreases in mean precipitation KO = 0.5(θ 700 + θ 500 − θ 1000 − θ 850 ) in JJA for all three realizations of ECHAM5 downscaled by CLM7, and cases of increases in precipitation seems to be more related to natural variability than a result of climate change. Notice that those differences in the precipitation pattern related to the complex orography are not seen in Ban et al (2015), who with a similar model showed consistently decreasing intensities for the current domain.…”
Section: Precipitation Statisticsmentioning
confidence: 82%
See 4 more Smart Citations
“…Analysis performed for the Wagner et al (2012) paper (personal communication) shows similar decreases in mean precipitation KO = 0.5(θ 700 + θ 500 − θ 1000 − θ 850 ) in JJA for all three realizations of ECHAM5 downscaled by CLM7, and cases of increases in precipitation seems to be more related to natural variability than a result of climate change. Notice that those differences in the precipitation pattern related to the complex orography are not seen in Ban et al (2015), who with a similar model showed consistently decreasing intensities for the current domain.…”
Section: Precipitation Statisticsmentioning
confidence: 82%
“…Trenberth et al 2003), or rather a super-CCrate (Lenderink and van Meijgaard 2008;Berg et al 2013;Westra et al 2014). When comparing historical to end of century projections in the RCP8.5 scenario, Ban et al (2015) found an intensification of the extremes according to the standard CC-rate over the Alps and surrounding regions, while for the southern UK, Kendon et al (2014) found that the increase in convective precipitation was consistent with a super-CC-rate. The scaling between precipitation intensity and temperature is strongly affected by the inclusion or not of dry days in the calculation of the extreme percentiles (Ban et al 2015).…”
Section: Atmospheric Conditions Leading To Convective Precipitationmentioning
confidence: 97%
See 3 more Smart Citations